Entrepreneurship education and undergraduate students' self-employment intentions: do paid employment intentions matter?. Issue 7 (29th September 2020) - Otache, Innocent; Oluwade, Dorcas Omanyo; Idoko, Ele-Ojo Jeremiah
Abstract : Purpose: Undergraduate students have two opposing employment intentions, viz. self-employment intentions and paid-employment intentions (SEIs and PEIs). While a plethora of studies have explored the links between entrepreneurship education (EE) and SEIs, it has been noted that previous studies have ignored the effects of PEIs on the relationship between EE and SEIs. The purpose of this study, therefore, is to empirically explore the effects of PEIs on the relationship between EE and SEIs. Design/methodology/approach: This study adopted a descriptive research design and a self-reported questionnaire was administered to collect data from a randomly selected sample of 95 accounting students from two polytechnics in Nigeria. To test the hypotheses formulated, partial least squares structural equation modelling (PLS-SEM) was performed using SmartPLS. Findings: The results of Model 1 showed that EE had a significantly positive link with SEIs. On the other hand, the analysis of Model 2 revealed an inverse relationship between PEIs and SEIs. Furthermore, it was observed that the impact of EE on SEIs did not only reduce significantly when PEIs was added to Model 1 but also the relationship between EE and SEIs that was erstwhile statistically significant became nonsignificant. Practical implications: The findings have implications for EE curriculum developers, governments and career guidance counsellors. Originality/value: To the best of the authors' knowledge, this study is the first to provide empirical evidence of the effects of PEIs on the relationship between EE and SEIs. The findings provide important insights into the fundamental issue, which underlies the problem of graduate unemployment.